1992
DOI: 10.1128/aac.36.11.2370
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of zidovudine-induced fetal toxicity in pregnant mice

Abstract: The effects of zidovudine (AZT) on the fetus were investigated in pregnant mice by using parameters such as the number of fetuses, fetal size, and the fetal hepatic cell clonogenic assay. AZT caused dose-dependent toxicity to the fetus upon administration via drinking water to pregnant mice from days 1 to 13 of gestation. At the 0.5-mg/ml dose level, AZT caused a decrease in the number of fetuses to 12 from an average of 16.5 in control animals, and the fetal size (crown-rump length) was reduced from 10.5 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…These findings mirrored those previously noted in retrovirally infected mice which had been exposed to the drug through their drinking water during middle to late gestation; no adverse drug effects were detected in the offspring (13,14). We and others have found, however, that AZT results in death of mouse embryos when exposure occurs in the first half of gestation (7,21). Our experiments presented here demonstrated that the critical period of AZT toxicity toward mouse embryos is between ovulation and implantation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These findings mirrored those previously noted in retrovirally infected mice which had been exposed to the drug through their drinking water during middle to late gestation; no adverse drug effects were detected in the offspring (13,14). We and others have found, however, that AZT results in death of mouse embryos when exposure occurs in the first half of gestation (7,21). Our experiments presented here demonstrated that the critical period of AZT toxicity toward mouse embryos is between ovulation and implantation.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, it is important to investigate the toxicity of intragestational administration of HIV antimetabolites in order to enable rational application to humans. It previously has been demonstrated that AZT at concentrations that are readily achievable with conventional human dosing is lethal to murine embryos during early gestation (7,21). Direct exposure of embryos to AZT in vitro resulted in retarded cell division at 0.1 ,ug/ml and cell death at concentrations of 1 ,ug/ml and above (21).…”
mentioning
confidence: 99%
“…Zidovudine was associated with increased preimplantation mouse embryo loss in several studies, [15][16][17][18] but no congenital abnormalities were detectable. The possible mechanism of embryolethality of zidovudine was thought to be due to retarded cell division.…”
mentioning
confidence: 99%
“…One milliliter of Zidovir oral solution contained 10 mg of active Zidovudine and a dose of 50 mg/kg ZDV was given daily. The dose of ZDV was standardized to 50 mg/kg body weight from 70 mg/kg as used by Gogu et al (1992).…”
Section: Breeding Of Mice and Zidovudine Treatmentmentioning
confidence: 99%